悲歌一曲撼千古 ：《悲愤诗》与《孔雀东南飞》之比较 = Comparison between “Bei Fen Shi” and “Kong Que Dong Nan Fei” - 李俊贤 Lee, Chun Hsien (2010)
"Grief and Indignation Poems" (Bei Fen Shi) and "Peafowl Fly toward Southeast" (Kong Que Dong Nan Fei) are two poems written in the Jian An period, both are narrative poems written from a woman’s perspective. The two lead female characters were compelled to remarry under two different circumstances; one mourned for her country’s demise while the other was involved in marital tragedy. Both poems are filled with real intense emotions. The poem "Bei Fen Shi" is about a woman, who at that time was occupied an inferior societal position. At the same time, the poem depicts a history filled with tears and blood. On the other hand, "Kong Que Dong Nan Fei" is a story about a couple deeply in love but are forced to separate from each other, in the end Liu Lan Zhi and Jiao Zhong Qing have no choice but to sacrifice their lives in the name of love.